The Molecular-Kinetic Approach to Hydrolysis of Boron Hydrides for Hydrogen Production - Filiz, B. Coskuner; Figen, A. Kanturk (PLEIADES PUBLISHING LTD, 2019)
In this study, Langmuir-Hinshelwood and Michaelis-Menten kinetic models are applied to describe the kinetic behaviour of the Co-B catalyst in the hydrolysis of 0.12 M aqueous solutions of boron hydrides at temperatures from 22 to 60 degrees C. Boron hydrides are selected as sodium borohydride (NaBH4, 10 wt % NaOH) and ammonia borane (NH3BH3). Based on the Langmuir-Hinshelwood kinetic approach, it is found that under the same reaction conditions the NaBH4-Co-B catalyst interaction is more effective than that of the NH3BH3-Co-B. According to the Langmuir-Hinshelwood model, apparent activation energies (E-a) for the hydrolysis of NaBH4 and NH3BH3 over Co-B catalysts are calculated to be 45.38 and 57.37kJ/mol, respectively.
Keywords: boron hydrides; hydrolysis; Co-B catalyst; Langmuir-Hinshelwood; Michaelis-Menten; COST-EFFECTIVE CATALYST; SODIUM-BOROHYDRIDE; AMMONIA-BORANE; GENERATION; NANOPARTICLES; DEHYDROGENATION; Chemistry